Parental leave length and mothers' careers: What can be inferred from occupational allocation? - Barbara Pertold-Gebicka (Charles University in Prague, Institute of Economic Studies (IES), 2019)
This paper shows that the time spent on parental leave affects mothers' careers several years after childbirth. It also shows that policy-relevant conclusions can be drawn from occupational allocation data even in the absence of individual wage or earnings information. I take advantage of a legislative reform that changed the duration of parental benefit payments effective in the Czech Republic in 2008. Introducing the possibility of the flexible timing of benefit collection over the period of two to four years, as opposed to the only option of four years before, the reform significantly increased the share of mothers returning to work before their youngest child turns four. This further translates to increased representation of employed mothers in high-skilled occupations and increases the average occupation wage of the affected mothers six to eight years after childbirth. These findings indicate that shorter leaves are beneficial for mothers' careers, at least in the medium run.
Keywords: J16; J13; J24; 330; Parental leave length; parental benefits; occupational allocation